The Mission in the Reformation Era: Literature Review of Church Strategy Models in the Mission Movement : English - Semuel Oktavianus Kairupan; Nobel Dilen Methusala; Jussintha Ria; Jaineke Lumika (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
Abstract In this article, literature research is discussed on the dynamics and strategic models of the church in the mission movement during the Reformation era. The theological understanding of the church's practice of mission underwent a major shift during the Protestant Reformation. This included the shift in authority from the ecclesiastical hierarchy to the authority of Scripture and the emergence of new methods to spread the gospel. This study investigates how Reformation figures such as Martin Luther, John Calvin, and other reformers influenced the missions paradigm through their writings, teachings, and church structures. In addition, it investigates modelsof various mission strategies that originated from the Reformation movement; these include Bible translation, local congregation-based evangelism, and education as a means of mission. This literature review shows that the Reformation era created new theologies and church mission strategies that are relevant for today.